Comparative evaluation of the therapeutic efficacy of rumen buffers and direct fed microbials (DFM) in sub-acute ruminal acidosis in dairy cows - S. Kumar Unni; C.G. Umesh; Magna Thomas; O.K. Sindhu; S. Ajithkumar (Journal of Veterinary and Animal Sciences, 2022)
Sub-acute ruminal acidosis (SARA) in dairy cattle is a disorder of ruminal fermentation caused by the ingestion of large amounts of concentrates with inadequate amounts of fibre. The condition is characterized by sustained and marked decrease in rumen liquor pH ≤5.5 for at least three hours of each day. Rumen buffers and direct fed microbials (DFM) are dietary supplements that had been used in the management of SARA. Rumen liquor samples of dairy cows from the organized farms and households of Wayanad district which were at the risk of SARA were collected by rumenocentesis for rumen pH estimation. Blood samples were collected from cows positive for SARA and subjected to haemato-biochemical evaluations. Three different therapeutic protocols involving oral administration of sodium bicarbonate, Lithothamnium calcareum extracts as rumen buffers and a mixture Saccharomyces cerevisiae and Aspergillus oryzae as direct fed microbial were compared in SARA positive cows for 14 days and the efficacy of the treatment was evaluated by the improvement in rumen liquor pH after the treatment period. Rumen buffer like sodium bicarbonate was found to be more efficient than Lithothamnium calcareum and DFMs like Saccharomyces cerevisiae and Aspergillus oryzae mixture in improving the rumen pH values in cattle positive for SARA.